Penerapan SAK ETAP pada Laporan Keuangan BUMDes Pondok Makan Puri Kencono Desa Karangawen - Arizka Novi Claudia; Ahmad Sahri Romadon (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2026)
This study aims to analyze the management of financial statements of Village-Owned Enterprises (BUMDes) in Karangawen Village, Karangawen Subdistrict, Demak Regency, particularly in the application of the Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP). The main objective of this study is to determine the extent to which the application of these accounting standards can improve the quality, transparency, and accountability of BUMDes financial statements in the local village environment. The method used in this research is descriptive qualitative, with data collection through interviews, observation, and documentation. Through this approach, researchers can deeply understand the process of planning, implementation, challenges, and quality in the management of financial statements. Interviews were conducted with BUMDes managers, while observation and documentation were used to support the validity of the data obtained. The results showed that the management of financial statements at BUMDes Pondok Makan Puri Kencono Karangawen Village has been running well. The financial statements prepared have referred to and are in accordance with the principles of SAK ETAP, thereby increasing transparency and accountability in BUMDes financial management. In conclusion, the application of SAK ETAP to this BUMDes has had a positive impact on better financial report governance.   Keywords: Accounting, SAK ETAP, Financial Statements, BUMDes